Effect of changing mesopic and photopic light conditions on visual functions - Fatemeh Mosayebi; Seyyed Mehdi Tabatabaee; Haleh Kangari; Saeed Rahmani (International Journal of Ophthalmology, 2023)
AIM: To determine the effects of change in light conditions on refractive error and visual functions including visual acuity, stereopsis and contrast sensitivity. METHODS: This cross-sectional study was conducted in the optometry clinic of the Shahid Beheshti School of Rehabilitation on 48 students in 2021-2022. All of them had eye health and normal visual function and could have refractive errors or not. Light intensity of 4 lx was considered equivalent to photopic light condition and light intensity of 1 lx was considered to be equivalent to mesopic light condition. The amount of refractive error was checked by auto refractometer and its changes in mesopic light condition were subjectively measured. Also, visual acuity, stereopsis and contrast sensitivity (in five spatial frequencies of 1.5, 3, 6, 12, and 18 cycles per degree), were measured first in photopic light condition and then in mesopic light condition, by Snellen control vision chart, stereo butterfly test and the M&S technology monitor test respectively. RESULTS: In the 48 student subjects with an average age of 22.69±3.56y, mean of refractive error as sphere equivalent, visual acuity and stereopsis were -1.25±1.74 diopters, 0 logMAR, 44.37±13.03 seconds of arc, respectively in photopic light condition while in mesopic light was equal to -1.56±1.75 diopters, 0.12±0.09 logMAR and 50.62±33.35 seconds of arc, respectively. The mean of contrast sensitivity measured at spatial frequencies of 1.5, 3, 6, 12, and 18 cycles per degree in photopic condition was equal to 2.38±0.04, 2.37±0.07, 2.04±0.21, 1.27±0.32, 0.82±0.27 logarithm of contrast sensitivity, respectively and in mesopic lighting condition was equal to 2.34±0.12, 2.30±0.16, 1.84±0.28, 1.02±0.28, 0.63±0.24 logarithm of contrast sensitivity, respectively. Statistical analysis showed a significant difference between the two lighting conditions in all evaluated variables [refractive error (P<0.001), visual acuity (P<0.001), stereopsis (P=0.008) and contrast sensitivity (P<0.001)]. CONCLUSION: The refractive error of the student subjects in mesopic light condition change towards myopia, and its amount is clinically significant. Also, the examination and comparison of the factors of visual acuity, stereopsis and contrast sensitivity in these two lighting conditions show that the decrease in brightness level to the mesopic level causes a decrease in the aforementioned visual functions.